Analysis of E-Samsat Delivery Services in Improving Public Services at Bappenda NTB - Alinda Dewi Trisnawati; Masri Yanti Sahputri; Ainur Fadilah; Esa Dwi Andika; Lisa Andriani; Zakiyah Hasanah; Cahyadi Kurniawan (CV. Abhinaya Indo Group, 2025)
This research was conducted at the office of the NTB Provincial Regional Revenue Management Agency, with the aim of finding out how the samsat delivery application service is in improving public services and the factors that hinder tax payment services using the samsat delivery application for the community. This type of research is qualitative descriptive, the selection of informants for this research is carried out by purposive sampling technique with 3 employees of Bappend NTB as key informants, and making the community as the main informant or users of the samsat delivery application as many as 3 people. The data sources in this study use primary and secondary data, for the data collection methods used, namely observation, documentation, and interviews. The data analysis used is data reduction, data presentation, and drawing conclusions and validating data in this study using tringulation of sources and methods. The results of this study show that of the six indicators of good public services based on law number 25 of 2009, namely public interest, professionalism, openness, participation, punctuality, and speed (ease and affordability), in the samsat delivery application. There are only 2 indicators that are not yet effective, namely the indicators of openness and participation. So it can be concluded that the analysis of the samsat delivery application service in reminding public services at Bappend NTB has been said to be effective. Although there are still obstacles in services such as a lack of human resources, applications that are not optimal, and a lack of socialization in the community.